Intuition, Imagination, and Philosophical Methodology. - Gendler, Tamar Szabó (OUP Oxford, 2010)
Tamar Gendler draws together a series of essays in which she investigates philosophical methodology, and shows the value for philosophy of empirical psychology. Three intertwined themes run through the volume: imagination, intuition and philosophical methodology.